PENGARUH EMOSI BELANJA DAN PROMOSI PENJUALAN TERHADAP PEMBELIAN TIDAK TERENCANA: Studi Kasus Pada Hypermarket Giant Pondok Cabe, Pamulang Timur - Niko Prima Rhamadhan, - (2019)
This research is quantitative which aims to determine the effect of emotional shopping and sales promotions on unplanned purchases. The population in this study were giant Hypermarket visitors. The variables used in this study are emotional shopping and sales promotion as independent variables, then unplanned purchases as the dependent variable.The sample size was taken as many as 50 respondents, with non probability sampling method, especially purposive sampling. Data collection is done through questionnaires. In this study three hypotheses were developed to be tested using PLS (Partial Least Square) analysis tools.The result of this study showed that (1) the shopping emotions significantly affect the unplanned purchases with the coefficient percentage as big as 0,851. (2) the sales promotion not significantly affect the unplanned purchases with the coefficient percentage as big as -0,117.